Percutaneous angioplasty of internal jugular and azygous veins in patients with chronic cerebrospinal venous insufficiency and multiple sclerosis: early and mid-term results. (July 2014) - Radak, Djordje; Kolar, Jovo; Sagic, Dragan; Ilijevski, Nenad; Tanaskovic, Slobodan; Aleksic, Nikola; Marinkovic, Jelena; Mitrasinovic, Anka; Radak, Sandra; Babic, Srdjan; Matic, Predrag; Vlajinac, Hristina
Purpose: To assess the safety of endovascular treatment of chronic cerebrospinal venous insufficiency (CCSVI) in patients with multiple sclerosis (MS). Materials and Methods: A total of 72 patients with CCSVI and MS (44 with relapsing remitting – RR, 4 with primary progressive, 20 with secondary progressive and 4 with benign MS) underwent percutaneous angioplasty. Outcome measures were colour Doppler ultrasonography parameters, gradient pressure at the vein abnormality level, postoperative complications, re-stenosis, disease severity scored by means of Expanded Disability Status Scale (EDSS) and patients' assumption of disease status. Controls were done after one month on 72 patients, six months on 69 patients and one year on 61 patients, respectively (the average follow-up was 11 months). Results: There were no postoperative complications. Colour Doppler ultrasonography showed significant improvement in cross-sectional area parameters ( P < 0.05) and significant decrease in confluence velocity values ( P < 0.05). Postoperative gradient pressure decreased, in internal jugular vein (IJV) significantly ( P < 0.05). Re-stenosis appeared in 5.3% of patients. EDSS score was significantly improved ( P < 0.01) and about half of patients reported significant or mild improvement in disease status and none of them worsening of symptoms. Conclusion: Endovascular treatment of the IJV and azygous veins in patients with CCSVI and MS is a safe procedure with no post-procedural complications followed by significant improvement of IJV flow haemodynamic parameters and decrease in the EDSS score. Whether CCSVI percutaneous treatment might affect clinical improvement in patients suffering from MS is yet to be seen after completion of major multicentric clinical trials, still it seems like that this procedure is not negligible.